Thermoplastic fiber filtering material
By using technical means such as burning treatment and flame retardant in thermoplastic fiber filter materials, a uniform small melting junction and porous structure are formed, which solves the problems of uneven performance and high cost of existing filter materials, and achieves efficient dust removal and low cost effects.
Patent Information
- Application Number
- CN202510151730.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-12
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-02-12
AI Technical Summary
While existing filter materials achieve efficient dust removal and low cost, they have problems such as uneven filtering performance, high cost and short service life.
Thermoplastic fiber filter material is used to form uniform small melting junctions through burning treatment. Combined with the use of flame retardant and oil agent, the fiber cross structure and surface coating are optimized to form a porous structure to improve filtration performance.
It achieves better filtration performance and durability, reduces manufacturing costs and service life, and can meet the needs of ultra-low emissions and long-term use.
Smart Images

Figure SMS_3 
Figure SMS_4 
Figure SMS_5
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of filter materials, and in particular to a thermoplastic fiber filter material. Background Art
[0002] In the past decade, countries around the world have become more and more determined to control air pollution, and the emission requirements for industrial enterprises have become increasingly stringent. Dust particle pollution is an important aspect of air pollution. Dust emissions will directly increase PM2.5 and seriously threaten the life, health and safety of residents. Using dust removal equipment to remove dust from industrial production emissions is an effective means of dust removal. The quality of the filter material determines whether the dust emission can meet environmental protection requirements, and will also affect the operating cost and material cost. With the tightening of environmental protection reviews and the intensification of product price competition, how to achieve both low cost and high efficiency dust removal has become a basic requirement for filter material manufacturers.
[0003] In previous patents, there are also surface-treated filter materials. For example, the Chinese patent with publication number CN103816717B discloses a high-temperature filter material, which performs calendering and shaping on the filter material needle blank cloth, singeing and easy-to-clean surface treatment on the calendered filter material needle blank cloth, and impregnation of the treated filter material blank cloth with polytetrafluoroethylene emulsion. It has excellent filtering performance. At the same time, the powder cake peeling performance is also good during cleaning, which is easy to clean. Dust will not penetrate into the filter cloth, which can reduce the filtering resistance. However, the above effect is achieved because polyimide fiber is implanted into the surface layer of the filter material (dust-facing side) through a composite method to improve the filtering performance of the filter material. Since the polyimide fiber has a special-shaped (leaf-shaped) cross-sectional structure and has a large filtering surface area, the cost is extremely high, and the influence of the surface morphology achieved through post-processing on the filtering performance is not explained.
[0004] The Chinese patent with publication number CN105597425A discloses a process for processing water-resistant filter materials, including a singeing treatment step, a calendering treatment step and a waterproofing treatment step. The invention uses a process of first singeing and then calendering to make a water-resistant filter material, which can wash away individual surface attachments by washing, thereby ensuring that it can continue to be used, and has very good hydrolysis resistance, can be washed multiple times, and reused repeatedly. The application does not make any requirements for the density, size, and uniformity of the nodes after singeing, but only requires easy washing, which has limited effect on improving the filtering effect. Summary of the invention
[0005] The purpose of the present invention is to solve the above technical problems and provide a thermoplastic fiber filter material.
[0006] In order to achieve the above technical objectives and meet the above technical requirements, the technical solution adopted by the present invention is: a thermoplastic fiber filter material, including a filter layer, a non-filter layer, and an intermediate fabric reinforcement layer, the surface of the filter layer contains nodes generated by the melting of thermoplastic fibers, the average area of the nodes is less than or equal to 0.02 square millimeters, the CV% of the node area is less than or equal to 40%, and the number of nodes distributed in any 1 square millimeter area is 5 to 20.
[0007] Preferably: no less than 80% of the nodes are spherical or elliptical in shape, and the shapes of the other nodes are irregular, including but not limited to long strips and radial shapes. The fibers of the filter material are treated with a flame retardant, the flame retardant contains more than 50% ammonium polyphosphate, and the proportion of the flame retardant content in the filter material is 0.05-0.16wt%.
[0008] Preferably, the number of hairiness on the surface of the filter material with a height higher than 0.5 mm is less than 4 per square centimeter.
[0009] Preferably, a coating is attached to the surface of the fibers on the surface of the filter layer, the coating is evenly applied to the surface of a single fiber, and the fibers adhered to each other by the coating do not exceed 10% of the total number of fibers.
[0010] Preferably: the weight percentage of the thermoplastic fiber in the filter layer is greater than or equal to 50%, the melting point of the thermoplastic fiber is 170°C to 300°C, the surface of the thermoplastic fiber contains 0.05 to 0.5 weight percent of oil, the sizing agent accounts for 5% to 15% of the oil, and the emulsifier accounts for 10 to 40%.
[0011] Preferably, the sizing agent is a mixture of higher fatty acid diethanolamine salt and alkyl alcohol phthalamide, and the proportion of one of them is not less than 25%, and the emulsifier is a non-ionic emulsifier.
[0012] Preferably: the gram weight of the filter material is 300-900g / m 2 , the air permeability of the filter material is 8-15cm 3 / cm 2 / s.
[0013] Preferably, the filter material has a singeing step during processing, the flame height is controlled at 3-8 cm, and the distance between the filter material and the fire port is 60-90% of the flame height. A filter bag can be made from this filter material, and this filter bag is used in asphalt, cement kilns, waste incineration, thermal power generation, steel and other fields.
[0014] Compared with the traditional structure, the beneficial effects of the present invention are as follows: the present application provides a porous filter material, the pore structure of which is formed by the cross-arrangement of fibers, and has the characteristics of uniform pore size distribution, firm and durable surface fiber mesh cross structure, etc. Under the premise of the same fiber diameter, the filter material prepared according to this case has better filtering performance and can be applied to industrial dust removal, air filtration and other fields. Not only can it meet the demand for ultra-low emissions, compared with previous high-efficiency dust removal products, through a special surface singeing treatment different from the traditional method, it does not need to be covered with a PTFE membrane, and even ultrafine fibers can be used less or not at all. It has a lower manufacturing cost and a longer service life, and can achieve the effect of low cost and low emissions. The service life is also longer than that of general filter materials on the market, and has a broader application prospect. DETAILED DESCRIPTION
[0015] The present invention will be further described below.
[0016] A thermoplastic fiber filter material includes a filter layer, a non-filter layer, and an intermediate fabric reinforcement layer. The surface of the filter layer contains nodes generated by melting thermoplastic fibers. The melted nodes are generated by singeing. The average area of the nodes is less than or equal to 0.02 square millimeters. The CV% value of the node area is less than or equal to 40%. The number of nodes distributed under any 1 square millimeter area is 5 to 20. The melted nodes are evenly distributed on the surface of the filter material, which can effectively reduce the larger holes on the surface of the filter material, and have a good resistance effect to blowing during long-term use. After blowing, the holes are not easy to deform and enlarge. The above description of the area and distribution of nodes is to express the characteristics that the nodes need to be small and evenly distributed. When the average area of the nodes is greater than 0.02 square millimeters and the CV% of the nodes is greater than 40%, it means that there are too large molten nodes, which will block the flow of gas and affect the overall air permeability of the filter material, resulting in low air permeability and high pressure loss during actual use, which cannot meet the low pressure requirements; the number of molten nodes distributed in any 1 square millimeter area is to illustrate the uniformity of distribution. When the number of molten nodes in a certain 1 square millimeter area is less than 5, and the number in another area is more than 20, it means that the node distribution is very uneven. When filtering, the holes in places with fewer nodes become larger after the filter material is sprayed for a long time, resulting in powder permeability. In places with more molten nodes, the air permeability is poor, and the uneven filtration effect leads to poor pressure loss, which cannot meet the filtration requirements.
[0017] The thermoplastic fiber filter material has no less than 80% nodes in the shape of a sphere or an ellipse, and the other nodes are in irregular shapes such as a strip or a radial shape. The fibers of the filter material have been treated with a flame retardant, and the flame retardant contains more than 50% of ammonium polyphosphate, and the proportion of the flame retardant content in the filter material is 0.05-0.16wt%. The addition of the flame retardant helps to form uniform and small-area molten nodes. When the flame retardant is less than 0.05wt%, the effect is not obvious, and the formed molten nodes are large and uneven. When the flame retardant ratio exceeds 0.16wt%, the number of burned molten nodes is too small. Here, the flame retardant can be added to the filter material by surface treatment, or it can be melt-spun together with the thermoplastic particles after being mixed in the melt spinning stage. In addition, the flame retardant addition ratio is closely related to the flame retardant performance of the thermoplastic fiber itself. When the thermoplastic fiber is polyester, nylon and other fibers without flame retardant effect, 0.05-0.16wt% of the flame retardant is preferred; when the thermoplastic fiber is PPS and other fibers with flame retardant effect, 0.05-0.10wt% of the flame retardant is preferred. Compared with other flame retardants, ammonium polyphosphate has a better effect of organizing thermoplastic fiber droplets, so it can keep small and uniform melting nodes of the filter material after singeing.
[0018] After uniform singeing, the number of hairs on the filter felt surface with a height higher than 0.5 mm is preferably less than 4 / cm2. The fiber surface of the filter layer is attached with a coating, which is evenly applied to the surface of a single fiber, and the fibers adhered to each other by the coating do not exceed 10% of the total number of fibers. PTFE emulsion dipping or spraying is preferred to optimize the surface dust removal effect. However, the proportion needs to be controlled. Too much will cause the fibers to stick together, which will lead to a decrease in filtration performance.
[0019] The weight percentage of thermoplastic fiber in the filter layer of the filter material is greater than or equal to 50%, the melting point of the thermoplastic fiber is 170℃~300℃, the surface of the thermoplastic fiber contains 0.05~0.5% weight percentage of oil, in which the sizing agent accounts for 5%-15% and the emulsifier accounts for 10-40%. The sizing agent is a mixture of two of the higher fatty acid diethanolamine salt and alkyl alcohol phthalamide, and the proportion of one of them is not less than 25%. The emulsifier is a non-ionic emulsifier. Both the sizing agent and the emulsifier have the function of optimizing the melting node area CV% and distribution. The melting node distribution is preferably 7-14 melting nodes in any 1 square millimeter area. Adding the sizing agent according to the above ratio is conducive to reducing the node area CV%, making the size of the node more uniform. Adding the emulsifier according to the above ratio makes it easier to reach the most preferred range of the node distribution number. Higher fatty acid diethanolamine salt and alkyl alcohol phthalamide are the most effective sizing agents, and non-ionic emulsifiers are also the best emulsifiers.
[0020] The weight of the filter material is 300-900g / m 2, the air permeability of the filter material is 8-15cm 3 / cm 2 / s.
[0021] During the processing of the filter material, there is a singeing step, and the flame height is controlled at 3-8cm, more preferably 4-6cm, and the distance between the filter material and the burner is 60-90% of the flame height, that is, when the flame height is 5cm from the burner, the distance between the surface of the filter material and the burner is 3.0-4.5cm. The flame height and the distance from the burner to the filter material will also affect the size and distribution uniformity of the fusion node. The above range can better control the nodes on the surface of the filter material. A filter bag can be made from this filter material, which is used in the fields of asphalt, cement kilns, waste incineration, thermal power generation, steel, etc.
[0022] This case has low manufacturing cost and longer service life. After more than 3 years of long-term use, the filtration performance can still be maintained at more than 95% of the new product, which can achieve the effect of low cost and low emission. The service life is also longer than the general filter materials on the market.
[0023] The present invention is described in more detail by the following examples and comparative examples. The physical properties in the examples are tested by the following methods, and can also be tested by other methods.
[0024] [Size and distribution of fusion nodes] The surface of the sample was photographed using a scanning electron microscope, and 10 points were extracted from the surface of the filter material for sample preparation and testing. The test magnification of each point was 200 times. The number of nodes in each sample was counted, the size of each node was measured, the average area of the node, the CV% of the node area, and the number of nodes distributed in any 1 square millimeter area were calculated.
[0025]
Average pore size
[0026] The average pore size of the filter material is obtained by the following formula: , Where, d: fiber diameter (denier), ρW: Density of filter material (g / cm 3 ), ρp: Fiber density (g / cm3 ).
[0027]
Weight
[0028] [VDI collection efficiency, outlet concentration, pressure loss, and cycle time] The performance of the filter material is determined based on the VDI3926 "Standard Test Method for Evaluating Cleanable Filter Materials". The size of the test sample is 15 cm in diameter. The dust concentration fed is 5.0 ± 5 g / m 3 , the filtration wind speed is 2m / min (air volume 1.85m 3 / h). The experimental sequence is the initial 30 times + forced aging pulse spraying 10,000 times + the last 30 times. The method for the initial 30 times and the last 30 times is: as the running time increases, the pressure difference on both sides of the filter material will gradually increase. When the pressure difference reaches 1000Pa, the pulse air will clean the dust on the surface of the filter material, and then proceed to the next process. The process is repeated 30 times. During the experiment, the experimental time (t / s) and pressure changes are recorded, and the weight M (g) of the dust passing through the filter material is weighed. The forced aging pulse spraying process means that during the operation, the filter material is deashed at a time interval of 5s, the cleaning pressure is 5bar, and the number of cleaning times is 10,000.
[0029] The outlet dust concentration C = the weight of dust passing through the filter material M / (1.85×time t / 3600), the unit of the outlet dust concentration C is mg / Nm 3 , outlet concentration is less than or equal to 0.40mg / Nm 3 The outlet concentration is less than or equal to 0.25 mg / Nm 3 Excellent judgment.
[0030] The pressure loss is the pressure loss automatically recorded by the equipment after the last injection of the last 30 times. A pressure loss of 350Pa or less meets the requirements of this case, and a pressure loss of 300Pa or less is considered excellent.
[0031] The cycle time is the total time spent on the last 30 cycles.
[0032]
Durability (blow-off resistance)
[0033] Calculation method of porosity retention rate: .
[0034] Example 1: The polyester filter felt made of 2.0D polyester fiber is divided into a three-layer structure of a dust-facing surface layer, an intermediate base fabric reinforcement layer, and a non-dust-facing layer. The dust-facing surface layer fiber contains 0.3% oil agent, of which the sizing agent accounts for 8% and the emulsifier accounts for 25%. The sizing agent is a mixture of higher fatty acid diethanolamine salt and alkyl alcohol phthalamide in a ratio of 50:50, and the emulsifier is a non-ionic emulsifier. The dust-facing surface layer is also impregnated with a flame retardant, with a weight ratio of 0.14%, and ammonium polyphosphate accounts for 75% of the flame retardant.
[0035] The filter felt was used to perform a singeing treatment on the dust-facing surface. During the singeing process, the flame height was adjusted to 6 cm, the distance between the dust-facing surface of the filter felt and the burner was adjusted to 4.5 cm, and the singeing speed was 18 m / min. The obtained filter felt was tested for the melting point under a microscope. After testing, it was found that the average area was 0.005 mm 2 , the CV% of the node area is 18%, 1mm 2 The average number of nodes in the area is 13.
[0036] The singed filter felt was subjected to VDI test and VDI durability test, and the outlet concentration of VDI in the last 30 times was 0.22 mg / Nm 3 In the VDI durability test, after 50,000 sprayings, the average pore size retention rate was 99%, with almost no decrease.
[0037] Example 2: The polyester filter felt made of 2.0D polyester fiber is divided into a three-layer structure of a dust-facing surface layer, an intermediate base fabric reinforcement layer, and a non-dust-facing layer. The dust-facing surface layer fiber contains 0.3% oil agent, of which the sizing agent accounts for 8% and the emulsifier accounts for 25%. The sizing agent is a mixture of higher fatty acid diethanolamine salt and alkyl alcohol phthalamide in a ratio of 50:50, and the emulsifier is a non-ionic emulsifier. The dust-facing surface layer is also impregnated with a flame retardant, the weight ratio of the flame retardant is 0.10%, and the proportion of ammonium polyphosphate in the flame retardant is 60%. The singeing method, node state, and VDI performance refer to Example 2 in Table 1.
[0038] Example 3: The polyester filter felt made of 2.0D polyester fiber is divided into a three-layer structure of a dust-facing surface layer, an intermediate base fabric reinforcement layer, and a non-dust-facing layer. The dust-facing surface layer fiber contains 0.2% oil agent, of which the sizing agent accounts for 5% and the emulsifier accounts for 25%. The sizing agent is a mixture of higher fatty acid diethanolamine salt and alkyl alcohol phthalamide in a ratio of 50:50, and the emulsifier is a non-ionic emulsifier. The dust-facing surface layer is also impregnated with a flame retardant, the weight ratio of the flame retardant is 0.14%, and the proportion of ammonium polyphosphate in the flame retardant is 75%. The singeing method, node state, and VDI performance refer to Example 3 in Table 1.
[0039] Example 4 and Example 5: The proportion of emulsifier in the oil is changed. The proportion of emulsifier in Example 4 is 15%, and the proportion of emulsifier in Example 5 is 35%. Other conditions are the same as Example 1. This proves the effect of the change of emulsifier content on the number of melting nodes per unit area. The less emulsifier content, the fewer nodes, and the more emulsifier content, the more nodes. The singeing method is the same as Example 1, and the node state and VDI performance refer to Example 4 and Example 5 in Table 1.
[0040] Example 6, Example 7: Other conditions are the same as Example 1. In Example 6, the flame height is adjusted to 8 cm during singeing, the distance between the dust-facing surface layer of the filter felt and the burner is adjusted to 6 cm, and the singeing speed is 18 m / min. In Example 7, the flame height is adjusted to 3 cm during singeing, the distance between the dust-facing surface layer of the filter felt and the burner is adjusted to 2.3 cm, and the singeing speed is 18 m / min. The effect of singeing conditions on the average area of nodes is verified. The higher the flame height, the larger the node area, and the lower the flame height, the smaller the node area. For the node state and VDI performance, refer to Example 6 in Table 1 and Example 7 in Table 2.
[0041] Example 8, Example 9: Other conditions are the same as Example 1. In Example 8, the flame height is adjusted to 6 cm during singeing, the distance between the dust-facing surface layer of the filter felt and the burner is adjusted to 5.4 cm, and the singeing speed is 18 m / min. In Example 9, the flame height is adjusted to 6 cm during singeing, the distance between the dust-facing surface layer of the filter felt and the burner is adjusted to 3.6 cm, and the singeing speed is 18 m / min. The effect of singeing conditions on the number of nodes per unit area is verified. The larger the distance between the dust-facing surface layer and the burner, the more nodes per unit area. For the node status and VDI performance, refer to Example 8 and Example 9 in Table 2.
[0042] Example 10: Other conditions are the same as those of Example 1. The polyester fiber used on the dust-facing side of the filter felt in Example 10 accounts for 60%, and the remaining fibers are thermosetting acrylic fibers. Since acrylic does not have the characteristic of melting, the number of nodes per unit area is reduced. The node state and VDI performance refer to Example 10 in Table 2.
[0043] Example 11: The PPS filter felt made of 2.0DPPS fiber is divided into a three-layer structure of a dust-facing surface layer, an intermediate base fabric reinforcement layer, and a non-dust-facing layer. The dust-facing surface fiber contains 0.3% oil agent, of which the proportion of the sizing agent in the oil agent is 8%, and the proportion of the emulsifier is 25%. The sizing agent is a mixture of higher fatty acid diethanolamine salt and alkyl alcohol phthalamide in a ratio of 50:50, and the emulsifier is a non-ionic emulsifier. The dust-facing surface layer is also impregnated with a flame retardant, the weight ratio of the flame retardant is 0.07%, and the proportion of ammonium polyphosphate in the flame retardant is 60%. Since PPS fiber with flame retardant effect is used, compared with Example 1, even if the amount of flame retardant added is reduced, the effect of Example 1 can be achieved. The singeing method, node state and VDI performance refer to Example 11 in Table 2.
[0044] Example 12: Other conditions are the same as Example 10, and the polyester fiber used on the dust-facing surface of Example 12 is a fiber with a fineness of 1.OD. Due to the improvement effect of singeing on VDI performance, the VDI performance of Example 12 is not significantly improved compared with Example 10. The node state and VDI performance refer to Example 12 in Table 2.
[0045] Example 13: The polyester filter felt made of 2.0D polyester fiber is divided into a three-layer structure of a dust-facing surface layer, an intermediate base fabric reinforcement layer, and a non-dust-facing layer. The dust-facing surface layer fiber contains 0.3% oil agent, of which the sizing agent accounts for 8% and the emulsifier accounts for 25%. The sizing agent is a mixture of higher fatty acid diethanolamine salt and alkyl alcohol phthalamide in a ratio of 50:50, and the emulsifier is a non-ionic emulsifier. The dust-facing surface layer is also impregnated with a flame retardant, the weight ratio of the flame retardant is 0.14%, and the proportion of ammonium polyphosphate in the flame retardant is 35%. The singeing method, node state, and VDI performance refer to Example 13 in Table 3.
[0046] Example 14: The polyester filter felt made of 2.0D polyester fiber is divided into a three-layer structure of a dust-facing surface layer, an intermediate base fabric reinforcement layer, and a non-dust-facing layer, wherein the dust-facing surface layer fiber does not contain an oil agent. A flame retardant is added during the spinning process of the dust-facing surface layer fiber, and the weight ratio of the flame retardant is 0.14%, and the proportion of ammonium polyphosphate in the flame retardant is 75%. The singeing method, node state, and VDI performance refer to Example 14 in Table 3.
[0047] Example 15: 2. The PPS filter felt made of ODPPS fiber is divided into a three-layer structure of a dust-facing surface layer, an intermediate base fabric reinforcement layer, and a non-dust-facing layer, wherein the dust-facing surface layer fiber contains 0.3% of an oil agent, of which the sizing agent accounts for 8% and the emulsifier accounts for 25%. The sizing agent is a mixture of higher fatty acid diethanolamine salt and alkyl alcohol phthalamide in a ratio of 50:50, and the emulsifier is a non-ionic emulsifier. The dust-facing surface layer is also impregnated with a flame retardant, the weight ratio of the flame retardant is 0.02%, and the proportion of ammonium polyphosphate in the flame retardant is 25%. The singeing method, node state, and VDI performance refer to Example 15 in Table 3.
[0048] Comparative Example 1: The polyester filter felt made of 2.0D polyester fiber is divided into a three-layer structure of a dust-facing surface layer, an intermediate base fabric reinforcement layer, and a non-dust-facing layer. The dust-facing surface fiber contains 0.3% oil, of which the sizing agent accounts for 8% and the emulsifier accounts for 25%. The sizing agent is a mixture of higher fatty acid diethanolamine salt and alkyl alcohol phthalamide in a ratio of 50:50, and the emulsifier is a non-ionic emulsifier. The dust-facing surface is also impregnated with a flame retardant, with a weight ratio of 0.14%, and ammonium polyphosphate accounts for 75% of the flame retardant.
[0049] Different from Example 1, Comparative Example 1 is not singed and has no nodes.
[0050] The filter felt was subjected to VDI test and VDI durability test, and the outlet concentration of VDI in the last 30 times was 0.5lmg / Nm 3 In the VDI durability test, after 30,000 sprays, the average pore size retention rate was 89%.
[0051] Comparative Example 2: PPS filter felt made of 2.0DPPS fiber, no oil agent and no flame retardant, no burning, the tested VDI performance and durability are similar to those of Comparative Example 1, see Table 4 Comparative Example 2 for details.
[0052] Comparative Example 3: The polyester filter felt made of 2.0D polyester fiber is divided into a three-layer structure of a dust-facing surface layer, an intermediate base fabric reinforcement layer, and a non-dust-facing layer. The dust-facing surface layer fiber contains 0.3% of an oil agent, of which the proportion of a sizing agent in the oil agent is 8%, and the proportion of an emulsifier is 25%. The sizing agent is a mixture of a higher fatty acid diethanolamine salt and alkyl alcohol phthalamide in a ratio of 50:50, and the emulsifier is a non-ionic emulsifier. The dust-facing surface layer is also impregnated with a flame retardant, the weight ratio of the flame retardant is 0.14%, and the proportion of ammonium polyphosphate in the flame retardant is 75%. When singeing, the flame height is adjusted to 10 cm, the distance between the dust-facing surface layer of the filter felt and the burner is adjusted to 10 cm, and the singeing speed is 18 m / min. It can be seen that the node area on the surface of the obtained filter felt is too large. The node state and VDI performance refer to Comparative Example 3 in Table 4.
[0053] Comparative Example 4: The polyester filter felt made of 2.0D polyester fiber is divided into a three-layer structure of a dust-facing surface layer, an intermediate base fabric reinforcement layer, and a non-dust-facing layer. The dust-facing surface layer fiber contains 0.2% of an oil agent, and there is no sizing agent in the oil agent. The emulsifier accounts for 25%, and the emulsifier is a non-ionic emulsifier. The dust-facing surface layer is also impregnated with a flame retardant, and the weight ratio of the flame retardant is 0.14%. The proportion of ammonium polyphosphate in the flame retardant is 75%. When singeing, the flame height is adjusted to 6 cm, and the distance between the dust-facing surface layer of the filter felt and the burner is adjusted to 6 cm. The singeing speed is 18 m / min. It can be seen that the CV% of the node area on the surface of the obtained filter felt is too large. For the node state and VDI performance, refer to Comparative Example 4 in Table 4.
[0054] Comparative Example 5: The polyester filter felt made of 2.0D polyester fiber is divided into a three-layer structure of a dust-facing surface layer, an intermediate base fabric reinforcement layer, and a non-dust-facing layer. The dust-facing surface layer fiber contains 0.3% of an oil agent, and the sizing agent accounts for 8% of the oil agent. The sizing agent is a mixture of higher fatty acid diethanolamine salt and alkyl alcohol phthalamide in a ratio of 50:50, and there is no emulsifier. The dust-facing surface layer is also impregnated with a flame retardant, the weight ratio of the flame retardant is 0.14%, and the proportion of ammonium polyphosphate in the flame retardant is 75%. When singeing, the flame height is adjusted to 3cm, the distance between the dust-facing surface layer of the filter felt and the burner is adjusted to 2cm, and the singeing speed is 18m / min. It can be seen that the number of nodes per unit area of the obtained filter felt is too small. The node state and VDI performance refer to Comparative Example 5 in Table 4.
[0055] Comparative Example 6: The polyester filter felt made of 2.0D polyester fiber is divided into a three-layer structure of a dust-facing surface layer, an intermediate base fabric reinforcement layer, and a non-dust-facing layer. The dust-facing surface layer fiber contains 0.3% of an oil agent, of which the proportion of a sizing agent in the oil agent is 8%, and the proportion of an emulsifier is 60%. The sizing agent is a mixture of a higher fatty acid diethanolamine salt and an alkyl alcohol phthalamide in a ratio of 50:50, and the emulsifier is a cationic emulsifier. The dust-facing surface layer is also impregnated with a flame retardant, the weight ratio of the flame retardant is 0.14%, and the proportion of ammonium polyphosphate in the flame retardant is 75%. When singeing, the flame height is adjusted to 10 cm, the distance between the dust-facing surface layer of the filter felt and the burner is adjusted to 5.5 cm, and the singeing speed is 18 m / min. It can be seen that the number of nodes per unit area of the obtained filter felt is too large. The node state and VDI performance refer to Comparative Example 6 in Table 4.
[0056]
[0057]
[0058]
[0059]
[0060] The above embodiments of the present invention are merely examples to clearly illustrate the present invention, but are not intended to limit the protection scope of the present invention. All equivalent technical solutions also belong to the scope of the present invention. The patent protection scope of the present invention should be defined by the claims.
Claims
1. A thermoplastic fiber filter material, comprising a filter layer, a non-filter layer, and an intermediate fabric reinforcement layer, characterized in that: The surface of the filter layer contains nodes generated by melting of thermoplastic fibers, the average area of the nodes is less than or equal to 0.02 square millimeters, the CV% of the node area is less than or equal to 40%, and the number of nodes distributed in any 1 square millimeter area is 5 to 20.
2. The thermoplastic fiber filter material according to claim 1, characterized in that: No less than 80% of the nodes are spherical or elliptical in shape, and the other nodes are irregular in shape, including but not limited to long strips and radial shapes. The fibers of the filter material are treated with a flame retardant, the flame retardant contains more than 50% ammonium polyphosphate, and the proportion of the flame retardant content in the filter material is 0.05-0.16wt%.
3. The thermoplastic fiber filter material according to claim 1, characterized in that: The number of hairiness on the surface of the filter material with a height higher than 0.5 mm is less than 4 per square centimeter.
4. The thermoplastic fiber filter material according to claim 1, characterized in that: The fiber surface of the filter layer is attached with a coating, which is evenly applied on the surface of a single fiber, and the fibers adhered to each other by the coating do not exceed 10% of the total number of fibers.
5. The thermoplastic fiber filter material according to claim 1, characterized in that: The weight percentage of the thermoplastic fiber in the filter layer is greater than or equal to 50%, the melting point of the thermoplastic fiber is 170°C to 300°C, the surface of the thermoplastic fiber contains 0.05 to 0.5 weight percent of oil, of which the sizing agent accounts for 5% to 15% and the emulsifier accounts for 10 to 40%.
6. The thermoplastic fiber filter material according to claim 5, characterized in that: The sizing agent is a mixture of higher fatty acid diethanolamine salt and alkyl alcohol phthalamide, and the proportion of one of them is not less than 25%. The emulsifier is a non-ionic emulsifier.
7. The thermoplastic fiber filter material according to claim 1, characterized in that: The gram weight of the filter material is 300-900g / m 2 , the air permeability of the filter material is 8-15cm 3 / cm 2 / s.
8. The thermoplastic fiber filter material according to claim 1, characterized in that: The filter material has a singeing step during processing, the flame height is controlled at 3-8 cm, and the distance between the filter material and the fire port is 60-90% of the flame height. A filter bag can be made from the filter material.
Citation Information
Patent Citations
A high-temperature filter material production process for bag filters
CN103816717B
Processing method of washable filtering material
CN105597425A
Filter material and use thereof
CN101934173A
High-temperature filter material manufacturing technology for bag type dust removal
CN103816717A
Liquid filter cloth and manufacturing method and application thereof
CN109745773A